Specific heat of Teflon, Torlon 4203 and Torlon 4301 in the range of 30–400 mK. (April 2015) - Singh, V.; Garai, A.; Mathimalar, S.; Dokania, N.; Nanal, V.; Pillay, R.G.; Ramakrishnan, S.
Highlights: Specific heat of Teflon, Torlon 4203 and Torlon 4301 measured in 30–400 mK range. The present work reports the specific heat of Torlon 4301 for the first time. Specific heat data of Teflon and Torlon 4203 has been extended up to 30 mK. Abstract: The specific heat of amorphous polymers, Teflon, Torlon 4203 and Torlon 4301, has been measured in the range of 30–400 mK using thermal relaxation calorimetric technique. The data is consistent with the tunneling state models used to explain the observed unusual low temperature specific heat of amorphous polymers. Below 100 mK, the specific heat of Torlon 4301 is ∼3 times higher than that of Torlon 4203. Teflon has the lowest specific heat, ∼10 times lower than that of Torlon 4301.